Incorporation of tin in different types of pores in SBA-15: synthesis, characterization and catalytic activity - Sasidharan, M.; Kiyozumi, Y.; Mal, N. K.; Paul, M.; Rajamohanan, P. R.; Bhaumik, Asim (Microporous and Mesoporous Materials, 2009)
Mesoporous Sn-SBA-15 has been synthesized by three different methods Such as conventional hydrothermal route, using cocatalyst NH4F and in the presence of organosilane precursor. All the materials are thoroughly characterized by powder X-ray diffraction (XRD), SEM. TEM. N-2 sorption and surface area measurements, diffuse-reflectance UV-visible and FTIR spectroscopy. TG-DTA and elemental analysis through ICP. Nitrogen adsorption data, XRD patterns, and TEM observations Suggests that the textural properties are retained during the isomorphous substitution of silicon by tin. ICP chemical analysis indicates that tin can be substituted in the range of S-l/S-n = 69-162. UV-visible spectra of samples synthesized by the cocatalytic approach exhibit unique absorption band at 213 nm characteristics of tin atom substituted in the smaller pores (2-3 nm) located inside the walls of mesopores. Further, an additional band at 224 nm can be assigned to Sri atoms located in the distorted tetrahedral position along the primary mesopores. In contrary, only one absorption band centered at 224 nm is observed for all the samples synthesized by conventional hydrothermal as well as in the presence of organosilane precursor. F-19 NMR spectra confirmed (no signal) the absence of occluded F- ions in the samples made with NH4F. Observed high catalytic activity in Baeyer-Villiger oxidation and Meerwin-Pondorf-Verly reduction under the liquid-phase conditions suggest the incorporation of a portion of tin in the smaller pores for the Sn-SBA-15 materials synthesized through cocatalyst method. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Baeyer-Villiger oxidation; catalysis; Functionalization of mesopores; Meerwin-Pondorf-Verly reduction; Sn-SBA-15